2010
DOI: 10.1093/occmed/kqq062
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of low-dose ionizing radiation exposure on interventional cardiologists

Abstract: While cytogenetic results show higher chromosomal damage, some immune responses are stimulated or modulated immunologically in ICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 21 publications
6
30
1
6
Order By: Relevance
“…Studies demonstrate increased levels of chromosomal abnormalities in medical workers with low-level occupation radiation exposure below recommended limits [5,6]. At a small hospital in Italy where radiation protective measures were sporadic, orthopaedic surgeons had an increased cumulative cancer incidence, 29% *blinded manuscript versus 4% in unexposed workers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrate increased levels of chromosomal abnormalities in medical workers with low-level occupation radiation exposure below recommended limits [5,6]. At a small hospital in Italy where radiation protective measures were sporadic, orthopaedic surgeons had an increased cumulative cancer incidence, 29% *blinded manuscript versus 4% in unexposed workers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Results from several studies indicate that long-term low doses of ionizing radiation can lead to significant somatic DNA damage in professionally exposed physicians (11)(12)(13)(14), and our data demonstrate that interventional radiologists are exposed to a substantial cumulative radiation dose (34.1 mSv outside the TCs [unprotected body area] and 8.7 mSv at a protected body area [underneath the TCs]). Radiation awareness and use of equipment-mounted shielding seemed to be effective during our study, as indicated by a radiation exposure below the detector threshold in approximately 50% of the cases in our study.…”
Section: Vascular and Interventional Radiology: Lightweight Bilayer Cmentioning
confidence: 52%
“…The decreased CD27+CD19+/CD19+ cell ratio, which suggests impaired development of Th2 and humoral memory connected with CD27+CD19+ lymphocytes, is particularly adverse. No significant differences found in B cells of the exposed to LLIR workers and the control group are associated with the diversity of these cells [5,8]. The observed decrease of CD5+CD19+ cells percentage as well as of CD27+CD19+/CD19+ and CD5+CD19+/ CD19+ cell ratios may result from the lower serum level of interleukin -4 (IL-4) and IL-10 and higher interleukin -2 (IL-2) because IL-4 and IL-10 are pivotal for Th2 immune response and function of B cells, whereas IL-2 prefers Th1 and inhibits Th2 immune response [5,18].…”
Section: Resultsmentioning
confidence: 70%
“…No significant differences found in B cells of the exposed to LLIR workers and the control group are associated with the diversity of these cells [5,8]. The observed decrease of CD5+CD19+ cells percentage as well as of CD27+CD19+/CD19+ and CD5+CD19+/ CD19+ cell ratios may result from the lower serum level of interleukin -4 (IL-4) and IL-10 and higher interleukin -2 (IL-2) because IL-4 and IL-10 are pivotal for Th2 immune response and function of B cells, whereas IL-2 prefers Th1 and inhibits Th2 immune response [5,18]. Tobacco smoking reduces the level of IgG in human serum, whereas proportion of B cells in the peripheral blood of smokers was similar to that in the non-smokers [19].…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation